CONCEPT OF RULE OF LAW IN RELATED TO FREISS ERMERSSEN AUTHORITY ON WELFARE STATE - Rusnan Rusnan (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
The History of welfare state’s emergence, which explains when the concept of rechtsstaat was introduced in the 19th century and beginning of 20th century the circumstances was dominated by the idea that state and government is passive or intervention absence in citizen affairs except in public interest such as war and foreign relations. State only considered as “nachtwacther state” which means night watchman state, these ideas according to the prevailing of economic liberalism concept at that time were in control of “Laissez faire, laissez aller” argumentation means if every person was given the freedom to take care of each economy, the State economy itself will be healthy. But the result of liberalism, in 1931 economic crisis emerged, thus demolishing world economy. To cope with the economic crisis state aid is needed and resulting the state began entering public life and since that the theory of welfare state growing rapidly. Type of welfare state or modern state law explains that the principal tasks of the state is not only in law enforcement but also to achieve social justice (social gerechtigheid) for all the people, to reach that the public administration needs freedom (freiss Ermessen) or pouvoir discretionaire in carrying out its functions (bestuurszorg). As a logical consequence of widespread state intervention in all aspects of people’s lives in a welfare state it would appear the issues in the government conduct due to Freiss Ermerssen given by the public administration in making public policy, generate possibility of arbitrary action against citizens. But keep in mind that the Freiss Ermessen is to resolve the problems that appear suddenly as a consequence of crisis. Kaywords : Rule of Law, Freiss Ermessen, Welfare State